2016
DOI: 10.1093/nar/gkw152
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily conserved autoregulation of alternative pre-mRNA splicing by ribosomal protein L10a

Abstract: Alternative splicing of pre-mRNAs can regulate expression of protein-coding genes by generating unproductive mRNAs rapidly degraded by nonsense-mediated mRNA decay (NMD). Many of the genes directly regulated by alternative splicing coupled with NMD (AS-NMD) are related to RNA metabolism, but the repertoire of genes regulated by AS-NMD in vivo is to be determined. Here, we analyzed transcriptome data of wild-type and NMD-defective mutant strains of the nematode worm Caenorhabditis elegans and demonstrate that e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
38
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 73 publications
0
38
0
1
Order By: Relevance
“…A number of studies have reported negative feedback mechanisms in which protein levels are autoregulated by modulating alternative mRNA splicing followed by NMD (22,2731), but the molecular mechanisms underlying such autoregulation have been elucidated for only a few proteins (1517,31). One such case is PTB, for which a high concentration increases its binding to intron 10 of its mRNA; this increases exon 11 skipping, producing an mRNA that then undergoes NMD (16).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have reported negative feedback mechanisms in which protein levels are autoregulated by modulating alternative mRNA splicing followed by NMD (22,2731), but the molecular mechanisms underlying such autoregulation have been elucidated for only a few proteins (1517,31). One such case is PTB, for which a high concentration increases its binding to intron 10 of its mRNA; this increases exon 11 skipping, producing an mRNA that then undergoes NMD (16).…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence splicing reporters for the rpl‐1 gene, encoding L10a, revealed that the alternative splicing regulation occurs uniformly throughout the body. A short stretch of approximately 40 nucleotides between the two competitive 5′ splice sites, termed L10a regulatory element (L10ARE), is evolutionarily conserved in the orthologous introns of the L10a‐encoding genes . Splicing reporter‐based analyses demonstrated that L10ARE is necessary for splicing autoregulation by L10a in both C .…”
Section: Excellent Model For Pre‐mrna Processing In Vivomentioning
confidence: 99%
“…Studies in Caenorhabditis elegans have shown that it is not uncommon 332 among ribosomal proteins to be AS-NMD targets [25]. In particular, ribosomal proteins L3, L10a, and 333 L12 use an evolutionarily-conserved pathway to insert PTCs in their pre-mRNA [76][77][78]. Here we show 334 that exon 2 of RPS3 has an alternative upstream donor site that induces a frameshift and targets RPS3 335 pre-mRNA for degradation ( Figure 4c).…”
mentioning
confidence: 73%
“…Consistently with this, exon 2 338 of RPS3 pre-mRNA contains a cognate eCLIP peak of RPS3, suggesting autoregulatory negative feedback 339 loop with a poison 5'-splice site in this gene. Remarkably, the ribosomal protein L10a in Caenorhabditis 340 elegans uses exactly the same strategy of regulation by specifically switching the donor site of its intron 3 to 341 create an unproductively spliced mRNA [78].…”
mentioning
confidence: 99%
See 1 more Smart Citation